PROTECTION OF INFORMATION FLOWS IN MOBILE NETWORK STANDARDS CDMA2000 - Петренко, А. Б.; Єлізаров, А. Б.; Шматок, С. А.; Ващук, В. О. (Science-based technologies, 2014)
Exploring adopted and implemented standards for the operation of CDMA2000. The focus is currently on functioning authentication algorithm CAVE (Cellular Authentification and Voice Encryption). This algorithm is used as a multi-functional not only during the authentication , but also to generate the key used for encrypting voice data service messages . CAVE - is a software-compatible nonlinear mixing function. If the operator does not use an element , A-Key (Authentication Key), as is the case with imposing a generation data network to the previous one, it greatly simplifies the construction and performance of clones zlovmy - snykamy . Since 2005, proposed a new system for authenticating AKA (Authentication and Key Agreement), which uses the hash function SHA- 1 and fully implemented in CDMA2000 Rev C.